Phytosociological Investigations of the South Facing Slope of Gunung Ledang Montane Forests, Peninsular Malaysia - Asep Sumpena, Ekarelawan (1995)
Tree species (> 6 cm dbh) in forty 20 x 40 m sampling units (SUs) at the montane forests of Gunung Ledang were individually enumerated in terms of density, frequency, and basal area. Habitat factors (i.e. two of physiographic and six of soil factors) were measured. Physiographic factors measured for altitude and slope while soil factors for soil pH, soil moisture, total N, available P, and exchangeable K. The relationships between vegetation and habitat factors were investigated by canonical correspondence analysis (CCA). Two-way indicator species analysis (TWINSPAN) was used for vegetation classification. A total of 100 species were recorded. The three most important species (based on importance value) are Dacrydium beccarii, Gluta renghas, and Leptospermum flavescens. Less important species include Porterandia anisophylla, Cephalomappa lepidotula, and Fagraea racemosa. The average values of species number, density and basal area were relatively diverse among the SUs. A gradient analysis of CCA showed that altitude is best correlated with species/SUs distributions. TWINSPAN clustered the forty SUs into two groups which were statistically interpreted by discriminant analysis revealing that species composition was strongly correlated with altitude and soil pH.